Separation anxieties: Structural separation and technological diffusion in nascent fibre networks - Bronwyn Howell (International Telecommunications Society (ITS), 2014)
Vertical separation of upstream network operations from downstream retail activities, as the most extreme form of access regulation, has long been considered a legitimate regulatory remedy against use of market power in upstream infrastructure markets to engage in price- and non-price discrimination to foreclose competition in downstream retail markets. However, the remedy is increasingly being mandated for new networks, sometimes before any investment has been made. This paper uses theories of General Purpose Technologies and regulatory economics to consider how vertical separation - compared to both access regulation and no regulation - poses challenges to the ability to maximise scale economies at the early stage of a network life-cycle. This suggests greater caution in its use at this stage compared to middle and mature phases of the life-cycle. The theories are examined via case studies of two markets where vertical separation has been mandated for Fibre-to-the-Home networks - Australia and New Zealand - and one where it has not - the Netherlands. The case studies suggest that mandatory separation imposes additional constraints on the network owner's ability to achieve scale economies arising from rapid uptake of a new network relative to access regulation when it fails to replicate amongst any retailers the vertically-integrated operator's incentives to engage in aggressive early-stage marketing. Analysis also suggests that contractual limitations may have greater effect on the ability to achieve scale economies than structural impositions and ownership limitations.
Keywords: 330